Sistem Monitoring Kondisi dan Posisi Pengemudi Berbasis Internet of things - Reyana Yunindya Sabilla; Dodon Yendri (Universitas Andalas, 2021)
The high rate of accidents caused by human error is still a problem faced inIndonesia. Road accidents caused by fatigue and drowsiness are very seriousproblems that cause thousands of road accidents every year. This research aimsto create a system that can help prevent accidents caused by the driver'scondition. The system consists of three main components, namely embeddedsystems, real-time databases, and mobile applications. The embedded systemconsists of the Arduino Uno, Pulse Sensor, GPS Module, Push Button, andNodeMCU. Based on the tests performed, the system can distinguish male andfemale drivers based on the input of the Push Button received. The system readsthe driver's heart rate using a Pulse Sensor and monitors the driver's condition(normal, abnormal, and sleepy) on a straight road with an average error of1.69%. The system gets the driver's location using the GPS Module with theclosest error distance is 13.54 meters, and the farthest error distance is 18.66meters from the actual location. And the system can display data on real-timedatabases and mobile applications, as well as send Telegram notifications to thedriver's family smartphone via NodeMCU ith the fastest time difference is 5seconds and the longest time is 8 seconds in good internet conditions